Substantive accountability in Europe's new economic governance - Dawson, Mark 1983- (Cambridge University Press, 2023)
The EU has become an increasingly powerful economic actor but we lack research on how EU economic decision-makers can be held to account. This book argues that the EU suffers from important substantive accountability deficits I.e. while numerous procedures exist to hold institutions like the Commission and ECB to account, there are few mechanisms to contest the merit and impact of economic decisions. The book combines detailed empirical research on how accountability practices are evolving across different fields of EU economic governance with a novel conceptual framework to assess where accountability deficits lie and how they might be addressed. Combining leading research in law and political science, this book will be of interest to scholars with an interest in the questions of accountability and economic governance arising from the budgets, central banks and financial institutions of the European Union.